Determinants of Budgeting Consistency in Local Goverment– A Case of Sabang Local Goverment Indonesia - Heru Fahlevi; Islahuddin Islahuddin; Didi Wahyudi (Proceedings of AICS - Social Sciences, 2016)
This study aimed to examine the influence of human resource quality, budget politics and budget transparency for consistency of budgeting process with the leadership style as a moderating variable. The population of this study were all local government work units in (satuan kerja) kota Sabang – Aceh. The respondents were 163 people that consist of 34 budgeting information users and 129 head of divisions and subdivisions. The data used was primary data which was collected through questionnaires. The data analysis was performed using a regression model of interaction or moderate regression analysis (MRA). The results showed that the quality of human resources, budget politics, budget transparency and leadership style has positive influence on the consistency of the budgeting process either simultaneously or partially. The leadership style partially strengthen the link between the quality of human resources, budget politics and transparency with the consistency of the budgeting preparation process.